CNN1 Represses Bladder Cancer Progression and Metabolic Reprogramming by Modulating HIF-1α Signaling Pathway - Zhang, Zheng; Li, Xiaoqing; Ren, Shaokun; Zhang, Wei (Frontiers in Oncology, 2022)
Bladder cancer (BC) is the second most common urinary system malignant tumor around the whole world. It has reported that CNN1 was lowly expressed in BC tissues. However, the mechanisms of CNN1 on BC cells were unclear. Herein, we aimed to probe the specific influences of CNN1 on BC pathogenesis. Firstly, the expression level and prognostic power of CNN1 were surveyed in BC patients. Then CNN1 over-expression was executed to exhibit the influences of CNN1 on BC cells. The real-time PCR and western blotting were employed to detect by the mRNA and protein expression levels. CCK8 assay was utilized to examine cell proliferation, and transwell assay was executed to test cell invasion and migration. The corresponding kits were utilized to detect glucose absorption, lactate secretion and ATP level. BC cells overexpressing CNN1 were utilized to establish a nude mouse xenograft tumor model, and the tumor volume and tumor weight were detected. Nude mouse tumor tissues were used for immunohistochemical experiments to test the expression levels of Ki-67 and CNN1. The outcomes indicated that CNN1 was significantly lowly expressed in BC tissues and cells. Besides, low expression of CNN1 was concerned with poor prognosis. Moreover, over-expression of CNN1 repressed the proliferation, invasion and migration of BC cells. Furthermore, CNN1 over-expression decreased the protein levels of glycolysis-related protein GLUT1, PKM2 and LDHA. Then, the decreased mRNA and protein levels of HIF-1α and PDK1 were identified after CNN1 over-expression. The in-vivo assays verified the effects of aberrant expression of CNN1 in mice with BC. In conclusion, these findings suggested that CNN1 might modulate BC progression through activating HIF-1α pathway and CNN1 might be a promising marker for BC diagnosis.